2005
DOI: 10.1002/hep.20655
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model for cystic biliary dysgenesis in autosomal recessive polycystic kidney disease (ARPKD)†

Abstract: Autosomal recessive polycystic kidney disease (ARPKD) is an important cause of liver-and renal-related morbidity and mortality in childhood. Recently, PKHD1, the gene encoding the transmembrane protein polyductin, was shown to be mutated in ARPKD patients. We here describe the first mouse strain, generated by targeted mutation of Pkhd1. Due to exon skipping, Pkhd1ex40 mice express a modified Pkhd1 transcript and develop severe malformations of intrahepatic bile ducts. Cholangiocytes maintain a proliferative ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
64
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 19 publications
1
64
3
Order By: Relevance
“…This result is consistent with studies in which transient small interference RNA-mediated inhibition of Pkhd1 in cholangiocytes resulted in shortening and decreased formation of cilia, 29 but spatial and environmental differences between in vivo tissues and in vitro cell culture may lead to different results. Mouse models with a deletion of Pkhd1 exon 40 44 and genetargeted mutations in Pkd2 that cause distinct liver and/or kidney cysts 33,45,46 do not exhibit defects in ciliary structure in the affected epithelial cells, suggesting that the failure of renal epithelia to assemble primary cilia may not be the only factor leading to cyst formation in the kidneys. For example, a recent study showed that disruption of the extracellular matrix protein laminin ␣5, which is a major component of the tubular and glomerular basement membranes, also produces cystic kidneys in Lama5 mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with studies in which transient small interference RNA-mediated inhibition of Pkhd1 in cholangiocytes resulted in shortening and decreased formation of cilia, 29 but spatial and environmental differences between in vivo tissues and in vitro cell culture may lead to different results. Mouse models with a deletion of Pkhd1 exon 40 44 and genetargeted mutations in Pkd2 that cause distinct liver and/or kidney cysts 33,45,46 do not exhibit defects in ciliary structure in the affected epithelial cells, suggesting that the failure of renal epithelia to assemble primary cilia may not be the only factor leading to cyst formation in the kidneys. For example, a recent study showed that disruption of the extracellular matrix protein laminin ␣5, which is a major component of the tubular and glomerular basement membranes, also produces cystic kidneys in Lama5 mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, another published Pkhd1 mouse model, generated by disrupting exon 40, also yielded an in-frame product with the loss of amino acids 2160 to 2223 and resulted in cystic liver disease and portal tract fibrosis but no pancreatic or kidney abnormalities. 24 Two other murine models, Pkhd1 del2 25 and Pkhd1 del3-4 26 develop renal cysts but only in aged mice; none of the orthologous models recapitulate the severe neonatal phenotype seen in humans suggesting the possibility that species differences may play a role in the relative resistance of mouse kidneys to cyst formation because of mutation in Pkhd1. The location of the mutations in the genes may also affect the severity of the disease, hence the clinical lesion in mice, and this is borne out in human studies in which genotype-phenotype interactions have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…An engineered mouse mutation with disruption of exon 40 still produces a modified transcript because of exon skipping. 24 This mouse model shows bile duct proliferation with associated portal tract fibrosis and portal hypertension but does not have discernible abnormalities in the kidney. 24 More recently renal phenotypes have been described in two mouse models harboring hypomorphic mutations in Pkhd1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Mice with targeted mutation of Pkhd1 develop cystic biliary dysgenesis and portal fibrosis. 9 In the PCK rat, cholangiocytes possess short and malformed cilia that do not express fibrocystin. 10 -12 Despite the identification of the genetic defect of the disease, the pathophysiology of the bile duct dilation and hepatic fibrosis are not fully understood.…”
mentioning
confidence: 99%